Spin dynamics of 3He-B with dissipation for the general spin-orbital configurations - Kharadze, G.; Suramlishvili, N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The spatially homogeneous spin dynamics of the superfluid 3He-B with dissipation is considered for the general spin-orbital configurations. It is demonstrated that the possibility of new coherent spin- precessing modes appears explicitly in the equations of motion describing the relaxation of the spin variables towards various attractors (resonance states) found previously as the stationary solutions and observed experimentally.